The Behavioural Motivations of Police Officers Engaged in Domestic Abuse Incident Work - Daniel P. Ash (Grounded Theory Review: An International Journal)
This paper explores domestic abuse police work by considering the behavioural motivations of officers. It is underpinned by a study using classic grounded theory to examine how officers behave when carrying out police incident work in England. This study identifies that the motivating driver of officers engaged in domestic abuse incident work viz. their main concern, is the continual management of threats to their social identity. Officers seek to understand whether a particular incident’s circumstances provide them with an opportunity to behave like an archetypal British police officer. Upholding archetypal identity is their main concern, and officers resolve their main concern by balancing value and effort (the core-category in this study). The main concern and core category, as a theoretical framework, provide a grounded theory through which officer interactions can be understood as a continuum of behaviours, conceptualised as identity retreat and identity deconstruction. Officers alternate between these behaviour types when seeking to uphold their archetypal identity as they manage incident outcomes. This study has implications for police practitioners and policymakers seeking to understand the motivation of officers when engaged in domestic abuse work and its impact on incident outcomes and officer behaviours.